AN ALTERNATIVE to THE OVER-CONSUMPTION PRACTICE: FRUGALITY of IMMIGRANTS from BULGARIA LIVING in BURSA - Eklemezler, Sercan; Adiloğlu, Selda (My University, 2019)
The over-consumption practices of the consumption age have lately been attracting increasing attention by many academic disciplines. This attention focuses mainly on the consumer, but it seems too early to talk about any research interest on the non-consumer. This study tries to focus on a group of people as an example of who do not consume in the over-consuming world. While non-consumers are the starting point of this study, the population of the immigrants, who are said to be tight-fisted, comprises those who immigrated to Bursa from Bulgaria. 356 people selected from this population are the sample of the study. The claim that immigrants from Bulgaria are frugal is a premise of the study, and certain hypotheses were developed to test this premise. This study employs the survey technique, and the responses were analyzed with the application of Mann-Whitney U and Kruskal-Wallis H tests, and Spearmana’s rho correlation analysis. The findings revealed that the immigrants in question were generally frugal. Accordingly, it was concluded that those who migrated to Turkey in 1970-1979 are more frugal, and those immigrating from Kardzhali are less frugal compared to those who came from other cities. Finally, the continuity of the frugality behavior by the second-generation (born in Bursa) immigrants was found to be significant in terms of the continuity of the practices of this immigrant group.
Keywords: Sosyoloji; Kentsel Çalışmalar